In-hospital pulmonary rehabilitation after completion of primary respiratory disease treatment improves physical activity and ADL performance: A prospective intervention study. Issue 49 (10th December 2021) - Shimoda, Masafumi; Takao, Satoshi; Kokutou, Hiroyuki; Yoshida, Naoyuki; Fujiwara, Keiji; Furuuchi, Koji; Osawa, Takeshi; Nakamoto, Keitaro; Tanaka, Yoshiaki; Morimoto, Kozo; Yano, Ryozo; Okumura, Masao; et al.
Abstract: Introduction: Pulmonary rehabilitation improves the physical condition of patients with chronic respiratory disease; however, there are patients who cannot leave the hospital because of their low activities of daily living (ADLs), despite the completion of primary respiratory disease treatment and rehabilitation during treatment. Therefore, this study demonstrated that those patients recovered their ADLs through in-hospital pulmonary rehabilitation after treatment completion. Methods: We prospectively studied 24 hospitalized patients who had some remaining symptoms and showed low ADL scores of 9 points or less on the short physical performance battery after undergoing treatment for respiratory disease in Fukujuji Hospital from October 2018 to October 2019, excluding 2 patients who had re-exacerbation and 1 patient who could not be examined using the incremental shuttle walk test (ISWT). After completion of the primary respiratory disease treatment, patients moved to the regional comprehensive care ward, and they received pulmonary rehabilitation for 2 weeks. In the ward, patients who could not yet leave the hospital could undergo pulmonary rehabilitation for up to 60 days. Data were evaluated three times: upon treatment completion (baseline), postrehabilitation, and 3 months after baseline. The main outcome was an improvement in the incremental shuttle walk test (ISWT) postrehabilitation. Results: The median age of the patients was 80 (interquartile range (IQR): 74.8–84.5), and 14 patients (58.3%) were male. The ISWT distance significantly increased postrehabilitation (median [IQR]: 60 m [18–133] vs 120 m [68–203], P < .001). The Barthel Index (BI) ( P < .001), the modified Medical Research Council ( P < .001), and other scale scores were also improved. Among patients with acute respiratory diseases such as pneumonia, chronic obstructive pulmonary disease, and interstitial pneumonia, ISWT and other data showed improvement at the postrehabilitation timepoint. Ten patients who could perform examinations at 3 months after baseline were evaluated 3 months after taking baseline data prior to starting rehabilitation. The ISWT showed significant improvement 3 months after baseline compared to baseline ( P = .024), and the ISWT distance was maintained after rehabilitation. Discussion and conclusions: Physical activity, symptoms, mental health, and ADL status in patients who had not recovered after primary treatment completion for respiratory diseases could improve through in-hospital pulmonary rehabilitation.